2019
DOI: 10.1002/jbmr.3655
|View full text |Cite|
|
Sign up to set email alerts
|

The Novel p38 Inhibitor, Pamapimod, Inhibits Osteoclastogenesis and Counteracts Estrogen-Dependent Bone Loss in Mice

Abstract: Pamapimod (PAM) is a novel selective p38 mitogen‐activated protein (MAP) kinase inhibitor proved to be effective in rheumatoid arthritis in phase 2 clinical trial. However, its effect on osteoclast‐associated osteoporosis and the underlying mechanisms remain unclear. In this study, we showed that PAM suppressed receptor activator of nuclear factor‐κB ligand (RANKL)‐induced osteoclast formation via inhibition of p38 phosphorylation and subsequent c‐Fos and nuclear factor of activated T cells c1 (NFATc1) express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 43 publications
(73 reference statements)
1
20
0
Order By: Relevance
“…Postmenopausal osteoporosis is a systemic metabolic bone disease that affects more than 200 million women worldwide (Zhao K. et al, 2019). Postmenopausal osteoporosis caused by dysfunctions in bone remodeling causes low bone mineral density and microstructural changes, which decrease bone strength and increase bone fragility, leading to increased fracture risk (Chen et al, 2018;Zhao X. et al, 2019). It has been reported that one of three women older than 50 years will undergo osteoporotic fractures, which has a significant impact on the patients' daily activities and quality of life, as well as significant economic costs for both individuals and society (Eriksen et al, 2014;Lin et al, 2016;An et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postmenopausal osteoporosis is a systemic metabolic bone disease that affects more than 200 million women worldwide (Zhao K. et al, 2019). Postmenopausal osteoporosis caused by dysfunctions in bone remodeling causes low bone mineral density and microstructural changes, which decrease bone strength and increase bone fragility, leading to increased fracture risk (Chen et al, 2018;Zhao X. et al, 2019). It has been reported that one of three women older than 50 years will undergo osteoporotic fractures, which has a significant impact on the patients' daily activities and quality of life, as well as significant economic costs for both individuals and society (Eriksen et al, 2014;Lin et al, 2016;An et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Then, nuclear factor of activated T cells cytoplasmic 1 (NFATc1), the main transcription factor that regulates osteoclast differentiation, will be triggered to stimulate preosteoclast maturation (Jiang et al, 2019;Zhao K. et al, 2019). Maturational osteoclasts, which are characterized by tartrate-resistant acid phosphatase (TRAP) expression, can generate actin-bound sealing zones for attaching to the surface of bone, and osteoclasts then release proteolytic enzymes, such as cathepsin K (CTSK), which promote resorption pit formation (Lee et al, 2019;Zhao X. et al, 2019). Excessive osteoclastogenesis and bone resorption result in changes in trabecular bone mass and microstructure, leading to the potential risk of fracture; this indicates the need to find therapeutic approaches to prevent osteoporosis (Eriksen et al, 2014;Chen et al, 2019;Jacome-Galarza et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, timely and appropriate medical therapy is necessary for those patients. In recent years, increasing medicines have been recommended to help ameliorate the effect imposed by overactivation of bone-resorbing activity, such as bisphosphonates (Green, 2003), pamapimod (Zhao et al, 2019), cathepsin K inhibitors (Mukherjee and Chattopadhyay, 2016), and alendronate therapies (Park et al, 2020). However, these therapies exhibit a series of side effects, including increased risk of osteonecrosis, renal toxicity, and allergic reaction, and may not be recommended for long-term administration (Hinchy et al, 2013;Lungu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The specific primers we used are according to a previously report unless otherwise noted. 11,12,18,19 The primers are listed in Table S1.…”
Section: Quantitative Real-time Polymerase Chain Reaction (Qrt-pcr)mentioning
confidence: 99%